Performance Analysis of Direct Torque Controlled BLDC motor using Fuzzy Logic - V. Geetha; S. Thangavel (Institute of Advanced Engineering and Science, 2016)
The Brushless DC motor (BLDC) control is used in many of the applications as it is small in size and with low power which can drive in high speed and lighter compared to other motors.The electric vehicles are built with BLDC motors and also in ships, aerospace etc., The control of BLDC motors is done with sensors like hall effect sensor for sensing the positions. The speed control can be done with normal PI and PID controllers. Direct torque control (DTC) of the BLDC motor is important in many applications. In this paper BLDC motor is controlled with DTC using PI, PID and Fuzzy logic control. The comparison of the performance of the motor is analyzed with the Matlab simulation software.